Two-port laparoscopic appendectomy with the help of a needle grasper: better cosmetic results and fewer trocars than conventional laparoscopic appendectomy - Turgut Donmez; Oguzhan Sunamak; Sina Ferahman; Server Sezgin Uludag; Dogan Yildirim; Adnan Hut (Videosurgery and Other Miniinvasive Techniques, 2016)
Introduction : The two-port laparoscopic appendectomy technique (TPLA) lays between the conventional three-port trocar procedure and single-port laparoscopic appendectomy surgery. During TPLA, the appendix is suspended with stitches, resulting in perforation risk and difficulty in exploration. Aim : We used a needle grasper in TPLA to hang and manipulate the appendix. Material and methods: Thirty-four patients (10 female, 24 male) who underwent TPLA between February 2015 and November 2015 were analyzed retrospectively for patient demographics, duration of operation, laparotomy or conventional laparoscopy necessity, drain use, complications, and hospital stay periods. The needle grasper was inserted at the right under the abdominal quadrant (McBurney point) without an incision to hang and manipulate the appendix. Results : The mean age was 25.19 ±8.464 years; the mean body mass index (BMI) was 23.50 ±3.246 kg/m2. ASA scores were 1 and 2. The operations were completed without any additional trocar in 34 patients. The mean operation time was 57.03 ±3.814 min. There were no intraoperative complications in any patients. Three patients required a drain; all were discharged after drain removal. Thirty-one patients were discharged on the 1st postoperative day; three patients with drains were discharged on the 2nd day. The mean hospital stay period was 1.18 ±0.535 days. Conclusions : Using the needle grasper, the appendix was held and suspended and the mesoappendix was cauterized and skeletonized successfully in TPLA. Inserting a needle grasper into the abdominal cavity at the McBurney point to manipulate the appendix helps and does not leave a visible scar.